2014
DOI: 10.1007/s11626-013-9729-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characterization and tenogenic differentiation of mesenchymal stromal cells isolated from equine umbilical cord blood

Abstract: Mesenchymal stem cells (MSCs) isolated from umbilical cord blood (UCB) in equines have not been well characterized with respect to the expression of pluripotency and mesenchymal markers and for tenogenic differentiation potential in vitro. The plastic adherent fibroblast-like cells isolated from 13 out of 20 UCB samples could proliferate till passage 20. The cells expressed pluripotency markers (OCT4, NANOG, and SOX2) and MSC surface markers (CD90, CD73, and CD105) by RT-PCR, but did not express CD34, CD45, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…3c. The doubling time of cells in SVF solution cultured on TCPS dishes by the conventional culture method appeared to be approximately 2.0 days, which is similar to the doubling time reported by several investigators141727. The doubling time of the migrated cells from NY mesh filters having a pore size of 11 μm showed similar doubling time, whereas the doubling time of the migrated cells from the filter having pore size >20 μm that were cultured on PS dishes was longer than the doubling time of the cells in SVF solution cultured on TCPS dishes ( p  < 0.05).…”
Section: Resultssupporting
confidence: 87%
“…3c. The doubling time of cells in SVF solution cultured on TCPS dishes by the conventional culture method appeared to be approximately 2.0 days, which is similar to the doubling time reported by several investigators141727. The doubling time of the migrated cells from NY mesh filters having a pore size of 11 μm showed similar doubling time, whereas the doubling time of the migrated cells from the filter having pore size >20 μm that were cultured on PS dishes was longer than the doubling time of the cells in SVF solution cultured on TCPS dishes ( p  < 0.05).…”
Section: Resultssupporting
confidence: 87%
“…BMP‐7, ‐12, ‐13, and ‐14 have been implicated in the neoformation and repair of tendons, and BMP‐12 has specifically been shown to promote tendon differentiation and formation in vitro and in vivo . Multiple studies have shown that BMP‐12 alone is sufficient to promote tenogenic differentiation of MSCs in vitro , as observed through increased expression of tendon markers, including tenomodulin, decorin, and scleraxis . Interestingly, for rat MSCs on collagen sponges, increases in the expression of scleraxis and tenomodulin were observed over 14 days, after only 12 h of exposure to BMP‐12 on day 1.…”
Section: Soluble Signaling Cuesmentioning
confidence: 99%
“…[116][117][118] Multiple studies have shown that BMP-12 alone is sufficient to promote tenogenic differentiation of MSCs in vitro, as observed through increased expression of tendon markers, including tenomodulin, decorin, and scleraxis. 118,119 118 Equine BMSCs BMP-12 Increased tenomodulin and decorin expression by MSCs in BMP-12 on day 20 Park et al 123 Rat ADSCs GDF-5 Increased cell number at 100 ng/mL at days 3-12; increased expression of scleraxis and tenomodulin in 100 ng/mL, increased tenascin-C expression in 1000 ng/mL Zhang et al 130 Human Human BMSCs FGF versus EGF + TGF-␤1…”
Section: Matrix Mechanical Propertiesmentioning
confidence: 99%
“…Equine MSCs are commonly harvested from bone marrow or adipose tissue and are expanded in vitro before use in autologous transplants [1013]. The requirement to use surgical procedures to harvest cells from those locations has driven the search for other—less invasive—sources including whole blood, umbilical cord blood, or Wharton jelly [1417]. In that regard, the endometrium represents an attractive alternative source of MSCs in the horse.…”
Section: Introductionmentioning
confidence: 99%